2021
DOI: 10.1021/acsnano.1c01567
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Bi2Sr2CaCu2O8+δ Nanosheets for Ultrafast Photonics and Optoelectronics

Abstract: Two-dimensional (2D) Bi 2 Sr 2 CaCu 2 O 8+δ (BSCCO) is a emerming class of 2D materials with high-temperature superconductivity for which their electronic transport properties have been intensively studied. However, the optical properties, especially nonlinear optical response and the photonic and optoelectronic applications of normal state 2D Bi 2 Sr 2 CaCu 2 O 8+δ (Bi-2212), have been largely unexplored. Here, the linear and nonlinear optical properties of mechanically exfoliated Bi-2212 thin flakes are syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…Thus, MnO 2 will be an ideal platform for testing soliton concepts and revealing evolutionary dynamics in light lasers. [ 77–81 ]…”
Section: Methodsmentioning
confidence: 99%
“…Thus, MnO 2 will be an ideal platform for testing soliton concepts and revealing evolutionary dynamics in light lasers. [ 77–81 ]…”
Section: Methodsmentioning
confidence: 99%
“…With the decrease of layers, the excitonic absorption and emission bands showed gradual blue-shift. Furthermore, 651 The experimental results showed that 2D Bi-2212 had great capability for plasmon absorption in the near-infrared wavelength range, as well as nonlinear absorption, through tailoring the thickness (Figure 44c).…”
Section: Controlling the Layer Number By Mechanical Peelingmentioning
confidence: 96%
“…The discovery of graphene and other two-dimensional (2D) materials has opened an entirely new field of research in material science. They became the most studied materials over the past decade. The monolayers of transition metal dichalcogenides (TMD) have a direct bandgap, which makes them promising candidates for optical and nanoelectronics devices. There are many techniques capable of obtaining monolayers of 2D-TMD, from which the most straightforward is the mechanical exfoliation of bulk crystals. However, this approach is not reproducible and scalable.…”
Section: Introductionmentioning
confidence: 99%